ICT Skills for the Success in African Green Energy Sector - Olek, Krystian; Krzos, Grzegorz (Publishing House of Wroclaw University of Economics and Business, 2024)
[The book focuses on IT/ICT skills, which are an integral element of the construction, development, and effective operation in the renewable energy sector. The development of technology, the creation of innovations in the industry, and the improvement of competencies are based on knowledge and skills in using IT tools. Therefore, the present manual addresses the educational and business sectors in the area of green energy in Africa, which will allow one to acquire basic IT/ICT knowledge applicable to the current stage of the sector’s existence.] z zapowiedzi
Olek, K.; and Krzos, G. (2024). ICT Skills for the Success in African Green Energy Sector. Publishing House of Wroclaw University of Economics & Business.
Keywords: ICT skills; low-code; no-code; green energy sector; mobile applications